2008
DOI: 10.1001/archgenpsychiatry.2007.16
|View full text |Cite
|
Sign up to set email alerts
|

Functional Magnetic Resonance Imaging of Methylphenidate and Placebo in Attention-Deficit/Hyperactivity Disorder During the Multi-Source Interference Task

Abstract: Methylphenidate OROS increased daMCC activation during the MSIT and may act, in part, by normalizing daMCC hypofunction in ADHD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
143
2
5

Year Published

2009
2009
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 177 publications
(165 citation statements)
references
References 117 publications
15
143
2
5
Order By: Relevance
“…Second, a single dose of MPH increased the right frontal NIRS signal (Figure 4b), thus confirming that MPH increased RIFC activation during an inhibitory control task (Rubia et al, 2014). Third, the change toward a level of prefrontal activation similar to that for HCs after the 4-to-8-week open trial (Figure 4c) is consistent with the results from a fMRI study of adults with ADHD (Bush et al, 2008) and an ERP study in children with ADHD (Sawada et al, 2010). Finally, our finding (Figure 4d) that long-term (1 year) MPH treatment affected brain development in ADHD children is consistent with the findings of a prospective MRI study (Konrad et al, 2007).…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Second, a single dose of MPH increased the right frontal NIRS signal (Figure 4b), thus confirming that MPH increased RIFC activation during an inhibitory control task (Rubia et al, 2014). Third, the change toward a level of prefrontal activation similar to that for HCs after the 4-to-8-week open trial (Figure 4c) is consistent with the results from a fMRI study of adults with ADHD (Bush et al, 2008) and an ERP study in children with ADHD (Sawada et al, 2010). Finally, our finding (Figure 4d) that long-term (1 year) MPH treatment affected brain development in ADHD children is consistent with the findings of a prospective MRI study (Konrad et al, 2007).…”
Section: Discussionsupporting
confidence: 84%
“…Increases in LIFC activity were previously observed in patients with ADHD who performed an error-monitoring task after acute (Rubia et al, 2011) and 6 weeks-MPH treatment during interference inhibition (Bush et al, 2008). A change in activation in the single-dose trial toward the level in HCs indicated a better response to continuous administration of MPH.…”
Section: Discussionmentioning
confidence: 56%
“…The daMCC, located on the medial surface of the frontal lobe, refers to areas 24c 0 /32 0 in humans. The nomenclature of cingulate subdivisions has evolved over the past few decades (Bush, 2009;Bush et al, 2008;Vogt, 2005): for simplicity here, the daMCC is equivalent to the dorsal ACC (Bush and Shin, 2006;Bush et al, 2002) and broadly consistent with the older term, the ACC, used by studies above (Alexander et al, 1986;Posner and Petersen, 1990). The daMCC maintains strong reciprocal connections with other cognitive/attention and motor regions, including the DLPFC, parietal cortex, premotor cortex, and striatum.…”
Section: Cfp Attention Networkmentioning
confidence: 93%
“…Moreover, a metaanalysis of neuroimaging studies by Dickstein et al (2006) found the daMCC among a short list of brain regions that were hypoactive in ADHD patients relative to healthy controls. Recently, Bush et al (2008) used fMRI to show that 6 weeks of MPH significantly increased daMCC activation, as compared with placebo, in adults with ADHD. Similarly, an ERP study reported that stimulant treatment increased ACC activity .…”
Section: Functional Studies: Pet and Fmrimentioning
confidence: 99%
“…Our results are in partial agreement with data observed from a research performed with MSIT evaluated by means with functional magnetic resonance imaging. Children with ADHD, showed lower CFPCAN activation than controls 16 . Comparison must be made with careful, because technique differences between studies.…”
Section: Ern Usefulnessmentioning
confidence: 79%